Self-Selected Individual Music Therapy for Depression during Hospitalization for Cancer Patients: Randomized Controlled Clinical Trial Study - Widiyono Widiyono; Sri Setiyarini; Christantie Effendy (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Depression is a psychological distress that often occurs on cancer patients. Depression can increase patient perception about pain, resulting reduced drug efficacy and longer length of stay. Drug treatment for depression sometimes has side effects. Another intervention to decrease depression on cancer patients is music therapy. Music therapy might avoid polypharmacy in cancer patients. The purpose of this study was to determine the effects of self-selected individual music therapy toward depression of cancer patients.Methods: The method used in this study was the randomized control trial (RCT). Simple Random Sampling was assigned randomly by three researcher assistants to participants (N=70) of intervention and control group. The intervention used was self-selected individual music therapy (SeLIMuT). SeLIMuT was applied four times in 2 days with a duration of 15 minutes each session. Beck Depression Inventory (BDI) was employed for selection purposes. The data were analyzed using Mann-Whitney with p < 0.05 and 95% CI. The effectiveness of therapy was analyzed by the effect size test using abs r.Results: Based on the result of the bivariate analysis, there was an effect of giving self-selected individual music therapy to reduce depression with depression gap in both groups with p-value of 0.001 (p < 0.05). The value of the effect test obtained abs r = 0.82 (r > 0.5). At the end, the self-selected individual music therapy had moderate effect toward depression of cancer patients.Conclusions: Music therapy is safe, inexpensive, and easy to use, for and by patients. The nurse can safely recommend any of these interventions for depression on cancer patients. Specific selections or types of music may have different effects on different patients and may provide different effects at different time, so the use of self-selected individual music therapy is recommended.